MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMES): CATALYSTS FOR INCLUSIVE ECONOMIC DEVELOPMENT IN INDONESIA - Fitriadi, Agus; Sudarmiatin, Sudarmiatin; Wardana, Ludi Wishnu (PUSAT KEWIRAUSAHAAN UNIVERSITAS BALIKPAPAN, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a critical role in promoting inclusive economic development in Indonesia by fostering job creation, regional growth, and poverty alleviation. MSMEs account for over 99% of businesses in Indonesia and employ more than 90% of the workforce, particularly in rural areas. Despite their significant contribution to the economy, MSMEs face numerous challenges, such as limited access to finance, technology, and burdensome regulations. This paper employs a qualitative approach to analyze the contribution of MSMEs to inclusive economic development in Indonesia. The data used is secondary data based on the collection of literature in the form of journals, books, and official websites. Findings suggest that while MSMEs are essential to Indonesia's economic growth, their potential is hindered by barriers such as inadequate access to capital and digital tools. The solution that can be an alternative for these challenges through targeted policy measures and increased collaboration between government, private sector, and civil society, MSMEs can play a more substantial role in driving inclusive and sustainable economic growth in Indonesia